2014
DOI: 10.1371/journal.pone.0112339
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration of Human MSC for Ischemic Brain Injury in the Mouse: In Vitro and In Vivo Neuroregenerative Functions

Abstract: Intranasal treatment with C57BL/6 MSCs reduces lesion volume and improves motor and cognitive behavior in the neonatal hypoxic-ischemic (HI) mouse model. In this study, we investigated the potential of human MSCs (hMSCs) to treat HI brain injury in the neonatal mouse. Assessing the regenerative capacity of hMSCs is crucial for translation of our knowledge to the clinic. We determined the neuroregenerative potential of hMSCs in vitro and in vivo by intranasal administration 10 d post-HI in neonatal mice. HI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…These findings indicate that MSCs can protect neurons from HIBD. In addition, we found that MSCs can migrate out of the lateral ventricle to other areas of the brain, which is consistent with previous study that the chemoattraction of MSCs may guide MSCs home to the ischemic lesion site . Further study showed that MSCs transplantation induced autophagosomes both in vitro and in vivo after hypoxia‐ischemia stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicate that MSCs can protect neurons from HIBD. In addition, we found that MSCs can migrate out of the lateral ventricle to other areas of the brain, which is consistent with previous study that the chemoattraction of MSCs may guide MSCs home to the ischemic lesion site . Further study showed that MSCs transplantation induced autophagosomes both in vitro and in vivo after hypoxia‐ischemia stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, if input signals controlling tissue homeostasis are affected in aging and chronic diseases, many factors will affect optimal survival and function of transplanted cells. In addition to their differentiation capacity, ADSCs secrete many trophic factors and immunosuppressive molecules (Donega et al, ; Wang et al, ; Whone, Kemp, Sun, Wilkins, & Scolding, ). Therefore, the therapeutic capacity and the ability of ADSCs to repair injured tissue is likely the result of both cell differentiation and paracrine alone or in combination (Kim, Park, & Sung, ; Ooi, Dheen, & Tay, ; Whone et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…88 . That this mechanism may involve enhancement of endogenous, tissue-resident stem cell function was suggested by in vitro studies where human BM-MSCs were shown to induce mouse neural stem cells to differentiate into neurons, leading the authors to suggest that this property represents a reflection of the neuroregenerative potential observed in vivo 98 .…”
Section: Introductionmentioning
confidence: 99%